Gambaran Tingkat Kecemasan Pada Pasien Pre Operasi dengan Anestesi Umum dan Regional di Rumah Sakit Pluit - Siti Aminah; Nurjalila Nurjalila (Universitas Malahayati, 2026)
ABSTRACT Anxiety is an emotional state involving fear, unease, and worry about perceived threats. Excessive anxiety can trigger increases in blood pressure, heart rate, and respiratory rate, as well as increased cortisol levels, which can hinder post-operative wound healing. Nurses play a crucial role at every stage of surgical procedures, including providing clear explanations of the procedures to help reduce patient anxiety. Anesthesia is a crucial component of surgical procedures, and providing clear information about both the anesthetic and surgical procedures can help reduce patient anxiety before surgery. To know the description of the level of anxiety of pre-operative patients with general anesthesia and regional anesthesia. A descriptive study with a quantitative approach. The sample in this study was all 82 patients scheduled for surgery in the Pluit Hospital Surgical Room Installation between November and December 2025. The sampling technique used was random sampling. The majority of respondents were aged 36-45 years (23.2%), male (54.9%), high school education (43.9%), civil servant (81.7%), and had no history of surgery (70.7%). The majority of respondents underwent general anesthesia (70.7%) and had moderate anxiety levels (47.6%). Respondents undergoing regional anesthesia mostly experienced mild anxiety (66.7%), and respondents undergoing general anesthesia mostly experienced moderate anxiety (53.4%). The majority of respondents undergoing regional anesthesia experienced mild anxiety, while the majority of respondents undergoing general anesthesia experienced moderate anxiety. Nurses are expected to implement appropriate nursing interventions to help reduce patient anxiety levels before surgery. Keywords: Anxiety, Preoperative, General Anesthesia, Regional Anesthesia. ABSTRAK Kecemasan merupakan keadaan emosional yang melibatkan rasa takut, kegelisahan, serta kekhawatiran terhadap keadaan yang dipandang sebagai ancaman. Kecemasan yang berlebihan dapat memicu peningkatan tekanan darah, denyut jantung, serta frekuensi pernapasan, dan juga menyebabkan peningkatan kadar kortisol yang dapat menghambat proses penyembuhan luka pasca operasi. Perawat berperan penting di setiap tahap tindakan bedah, salah satunya dengan memberikan penjelasan yang jelas mengenai prosedur yang akan dilakukan guna membantu menurunkan tingkat kecemasan pasien. Anestesi merupakan bagian penting dalam pelaksanaan tindakan pembedahan, dan pemberian informasi yang jelas mengenai prosedur anestesi maupun pembedahan dapat membantu mengurangi kecemasan pasien sebelum operasi. Mengetahui gambaran tingkat kecemasan pasien pre operasi dengan anestesi umum dan anestesi regional. Deskriptif dengan pendekatan kuantitatif. Sampel dalam penelitian ini adalah seluruh pasien yang dijadwalkan menjalani operasi di Instalasi Kamar Bedah Rumah Sakit Pluit selama Bulan November sampai Desember 2025 sebanyak 82 orang. Teknik pengambilan sampel menggunakan random sampling. Mayoritas responden berumur 36-45 tahun (23,2%), jenis kelamin laki-laki (54,9%), pendidikan SMA (43,9%), pekerjaan PNS (81,7%) dan tidak ada riwayat operasi (70,7%). Mayoritas responden dengan anestesi umum (70,7%) dan tingkat kecemasan sedang (47,6%). Responden dengan anestesi regional mayoritas mengalami kecemasan ringan (66,7%), dan responden dengan anestesi umum mayoritas mengalami kecemasan sedang (53,4%).Responden dengan anestesi regional mayoritas mengalami kecemasan ringan dan responden dengan anestesi umum mayoritas mengalami kecemasan sedang. Diharapkan perawat dapat menerapkan intervensi keperawatan yang tepat agar dapat membantu menurunkan tingkat kecemasan pasien sebelum tindakan operasi. Kata Kunci: Kecemasan, Pre Operasi, Anestesi Umum, Anestesi Regional.